PUSAT KULINER DENGAN PENDEKATAN ARSITEKTUR METAFORA DI SURAKARTA - Ristiara Wantemas; Ofita Purwani; Sri Yuliani (Universitas Sebelas Maret Surakarta, 2016)
The potential of Indonesian culinary field is increasing every year, indicated by inflation in the business sector and culinary tourism. This suggests a potential in the culinary field to be developed. The strategy to support the national culinary development program includes improving the quality of education in the culinary field. Therefore it takes an educational space that is able to develop creative human resources in the culinary field. Culinary field is one of the promising areas in the development of Surakarta travel, so other than as an educational space, a culinary center can be a tourist attraction culinary Surakarta. Metaphor Architecture is used as an approach in the planning and architecture, considering that Metaphor Architecture can visually communicate the building functions to the public. Architectural Metaphor used is Tangible Architectural Metaphor, so that the form will be designed in such Metaphor to be able to communicate the existence of Culinary Center and Culinary landmark of Surakarta City. Problems in planning and designing Culinary Center ie what form it will be used as the basis of an analogy to be a metaphor ? Be used stages of creative thinking in design the Culinary Center with Metaphor Architectural Approach . Based on typical food survey Solo , liwet rice has the highest number of respondents as the most representative food the city of Solo , so liwet rice will be to the main idea into a form that will be used as a metaphor in designing Culinary Center.Keywords: Culinary Education, Culinary Center, Creative Thinking, Metaphor Architecture, Tangible Metaphor Architecture